Complications of extraperitoneal robot-assisted radical prostatectomy in high-risk prostate cancer: A single high-volume center experience - Paladini, Alessio; Cochetti, Giovanni; Felici, Graziano; Russo, Miriam; Saqer, Eleonora; Cari, Luigi; Bordini, Stefano; Mearini, Ettore (Frontiers in Surgery, 2023)
Introduction: The role of the robot-assisted radical prostatectomy (RARP) in high-risk prostate cancer (PCa) has been debated over the years, but it appears safe and effective in selected patients. While the outcomes of transperitoneal RARP for high-risk PCa have been yet widely investigated, data on extraperitoneal approach are poorly reported. The aim of this study was to evaluate intra- and post-operative complications in a series of patients with high-risk PCa treated by extraperitoneal RARP (eRARP) and pelvic lymph node dissection. Secondary aim was to report oncological and functional outcomes. Methods: Data of patients who underwent eRARP for high-risk PCa were prospectively collected from January 2013 to September 2021. Intraoperative and postoperative complications were recorded as well as perioperative, functional and oncological outcomes. Intraoperative and post-operative complications were classified by Intraoperative Adverse Incident Classification by the European Association of Urology and the Clavien–Dindo classification, respectively. Univariate and multivariate analysis were performed to evaluate a potential association between clinical and pathological features and the risk of complications. Results: 108 patients were included. The mean operative time and estimated blood loss were 183.5±44 minutes and 115.2±72.4 ml, respectively. Only two intraoperative complications were recorded, both of grade 3. Early complications were recorded in 15 patients, 14 of minor grade, 1 of grade IIIa. Late complications were diagnosed in 4 patients, all of grade III. BMI>30 kg/m2, PSA>20 ng/ml, PSA density>0.15 ng/ml2 and pN1 significantly correlated with higher rate of overall postoperative complications. Moreover, BMI>30 kg/m2, PSA>20 ng/ml and pN1 significantly correlated with higher rate of early complications while PSA>20 ng/ml, prostate volume <30 ml and pT3 were significantly associated with higher risk of late complications. In multivariate regression analysis PSA>20 ng/ml significantly correlated with overall postoperative complications, while PSA>20 and pN1 with early complications. Urinary continence and sexual potency were restored in 49.1%, 66.7% and 79.6% of the patients and in 19.1%, 29.9% and 36.2% of the patients at 3, 6 and 12 months, respectively. Conclusion: eRARP with pelvic lymph node dissection in patients with high-risk PCa is feasible and safe technique, showing few intra and post-operative complications, mostly of low grade.